Peta Konsep Pembelajaran Aqidah Akhlak - Misnan (Sekolah Tinggi Agama Islam Sumatera Medan, 2018)
The word morals comes from the Arabic plural khulq which means manners, mannerisms, habits or behaviour. By the term moral science experts are considered not yet right, then according to the more precise they are according to Al Ghazali in the team project the construction of the religion of Islam. So the nature of the learning of aqidah morals is what exactly the essence or foundation of beliefs and behavior (which is based on the inner shape) that good according to Islamic teachings and how human or process to learn it, so that the human understanding teaching well. For terms commonly used term, aqeedah Unity, the science of Kalam, the science of Usul, Theology, mentioning other types of science of kalam i.e. aqa'id Science (i.e. Science creed-creed i.e. node-node/belief, science of Tawhid (the science of keMaha Esaan (God) , and the science of Usul al-Din (i.e. the science of Usul trees religion). For terms commonly used term Shari'a fiqh, worship, muamalah, and moral terms for the commonly used term, tasauf and others. To develop material aqidah morals, then we need to know the magnitude of what material, what part of what's next. Or also called the structure of matter such as we learn about the material of gratitude, we know that it is commendable to God, morals